A Periodic "Self‐Correction" Scheme for Synchronizing Lithium Plating/Stripping at Ultrahigh Cycling Capacity. (13th March 2020) - Zou, Peichao; Chiang, Sum‐Wai; Zhan, Houchao; Sui, Yiming; Liu, Kangwei; Hu, Shengyu; Su, Songyang; Li, Jing; Kang, Feiyu; Yang, Cheng
Abstract: Lithium (Li) metal can deliver the highest theoretical specific capacity among all lithium battery anodes, yet its application is significantly hindered due to a series of critical challenges (poor cycleability and safety risks, etc.), most of which are related to uncontrolled Li dendrite growth. However, the dendrite problem cannot be fully avoided because of a number of complicated multi‐physical field factors, especially under high cycling rate and high capacity conditions. An ideal situation is when the battery can automatically restore the uncontrolled dendrites growth itself, whenever it appears during the entire cycling lifespan; however, discussion on this issue is rare. A periodically conductive/dielectric lamella scaffold is developed for hosting Li metal to realize a "self‐correction" functionality, which can automatically synchronize Li deposition/stripping by periodically re‐homogenizing electric field distribution around irregular Li protrusions. Consequently, dendrite‐free Li plating/stripping with high Coulombic efficiency can be achieved even at 5 mA cm −2 and an ultrahigh cycling capacity of 15 mAh cm −2 . Notably, a maximal cumulative plating capacity of 4000 mAh cm −2 with Li utilization of 50% is realized, outperforming most recently reported results. This work provides new insights for designing future smart high‐performance metal anode batteries for real application. Abstract : A periodically conductive–dielectric alternating layout is proposed to host lithium (Li) metal. Each conductive layer is electrically equipotential to re‐homogenize the local electric field, thus automatically and periodically smoothing the subsequent Li metal deposition, presenting a "self‐correction" behavior. As a result, stepwise and synchronized Li plating/stripping with high evenness can be achieved, even at both high current density and high cycling capacity.